2017
DOI: 10.21475/ajcs.17.11.11.pne548
|View full text |Cite
|
Sign up to set email alerts
|

Variance components and heritability of yield and yield components of wheat under drought-stressed and non-stressed conditions

Abstract: This study estimated the variance components and heritability of yield and yield related traits of a population of 96 diverse bread wheat genotypes under drought-stressed and non-stressed conditions. The genotypes were evaluated across eight testing environments during the 2014/2015 and 2015/2016 growing seasons using an alpha lattice design with two replications. Combined analysis of variance and variance components were analysed following the General Linear Model (GLM)'s procedure. Results indicated the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…Under stress condition the tested genotypes exhibited highly significant (P≤0.01) variation for all traits studied. Several types of research have been conducted on bread wheat under drought condition and found highly significant variation for the traits reported herein our study (Rehman et al 2015;Mwadzingeni et al 2017;Abd-Allah et al 2018;Pour-Aboughadareh et al 2020). In contrary to the present result non-significant variation was reported for biomass yield and harvest index (Sahar et al 2016) in wheat under drought condition.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Under stress condition the tested genotypes exhibited highly significant (P≤0.01) variation for all traits studied. Several types of research have been conducted on bread wheat under drought condition and found highly significant variation for the traits reported herein our study (Rehman et al 2015;Mwadzingeni et al 2017;Abd-Allah et al 2018;Pour-Aboughadareh et al 2020). In contrary to the present result non-significant variation was reported for biomass yield and harvest index (Sahar et al 2016) in wheat under drought condition.…”
Section: Resultscontrasting
confidence: 87%
“…Similar to the present result, Rehman et al (2015) reported moderate heritability value for spike length under drought condition in bread wheat. Grain yield is a polygenic trait that is highly influenced by the environment under stressed condition; thus moderate heritability was expected for this trait (Mwadzingeni et al 2017). The author also found moderate heritability value for grain yield under drought stress condition which support present finding.…”
Section: Estimates Of Broad Sense Heritability Expected Genetic Advance and Genetic Advance As Percentage Of Meansupporting
confidence: 81%
“…(2014) and Mwadzingeni et al. (2017) reported significant reduction in yield, seed size, plant height and tiller numbers due to drought stress, which were corroborated by the findings of this study. In contrast, drought stress resulted in an increase in root–shoot ratio, which implied that drought stress promoted root biomass accumulation or had higher negative impact on shoot compared with root growth in the mutant families.…”
Section: Discussionsupporting
confidence: 91%
“…Mwadzingeni et al. (2017) reported significant interaction between genotype and water regime influencing yield and yield component traits of wheat genotypes under contrasting water levels showing that water availability affects plant growth in general although the actual extent of impact is dependent on genetic constitution of the plant and the intensity of the stress. The selection of genotypes with superior agronomic performance and biomass allocation under drought stress could facilitate the development of cultivars adapted to water‐limited constrained environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation